Penataan Infrastruktur Kota Manado Masa Kolonial : Penataan infrastruktur Kota Manado 1824-1945 - Putra Kama Jaya; Pratama, Henki Riko; Marzuki, Irfanuddin Wahid; Sari, Vivi Sandra (Berkala Arkeologi, 2023)
This article discusses the arrangement of Manado city infrastructure carried out by the Dutch colonial government in 1824-1945. Manado City before being laid out and became the center of government of the North Sulawesi region was a traditional Minahasa settlement that lacked adequate infrastructure. The research method uses multidisciplinary archaeology, which combines archaeological methods with other disciplines (urban planning and spatial planning). The results showed that the arrangement carried out by the Dutch colonial government included a network of roads and bridges, ports, offices, defense, commerce, open space, and cemeteries. The infrastructure in Manado has undergone significant changes since the Dutch colonial era. Many colonial buildings that were damaged during World War II have either changed their function or been replaced by new buildings.